13 Medications that affect the lower oesophageal sphincter and risk of oesophageal cancer: a nested case-control study. (5th April 2017) - Spence, A; Busby, J; Murchie, P; Coleman, H; Johnston, B; Murray, L; Iversen, L; Lee, A; Cardwell, C
Abstract : Background: Excessive relaxation of the lower oesophageal sphincter results in increased gastro-oesophageal acid reflux, a risk factor for oesophageal cancer. Aim: We aimed to investigate the risk of oesophageal cancer in patients prescribed medications known to relax of the lower oesophageal sphincter. Method: Using the Scottish Primary Care Clinical Informatics Unit (PCCIU) database, a nested case-control study of Scottish patients diagnosed with oesophageal cancer between 1999 and 2011 was performed. Medication use was determined from GP prescription records. Conditional logistic regression was used to calculate OR and 95% CI for oesophageal cancer risk in patients prescribed benzodiazepines, calcium channel blockers, nitrates, respiratory sympathomimetics or xanthine medications. Results: A total of 1979 oesophageal cancer patients were matched to 9543 controls. There was a significantly increased risk of oesophageal cancer in patients prescribed respiratory sympathomimetics (adjusted OR 1.27, 95% CI 1.08–1.48) but no dose-response association was observed. No significant increased oesophageal cancer risks were seen for users of other medications that relax the lower oesophageal sphincter (adjusted OR for benzodiazepines 0.94, 95% CI 0.79–1.11; calcium channel blockers 1.05, 95% CI 0.92–1.20; nitrates 1.09, 95% CI 0.92–1.29; or xanthines 1.44, 95% CI 0.91–2.28). Conclusions: Respiratory sympathomimetic medication use was associated with an increased risk of oesophageal cancer. Oesophageal cancer risk was not significantly increased for users of other medications known as relaxants of the lower oesophageal sphincter. Further, the observed association may not be causal because there was no dose response relationship, and possible confounding due to asthma symptoms.